2024
DOI: 10.1038/s41598-023-51005-3
|View full text |Cite
|
Sign up to set email alerts
|

Immunoinformatics-guided approach for designing a pan-proteome multi-epitope subunit vaccine against African swine fever virus

Alea Maurice Simbulan,
Edward C. Banico,
Ella Mae Joy S. Sira
et al.

Abstract: Despite being identified over a hundred years ago, there is still no commercially available vaccine for the highly contagious and deadly African swine fever virus (ASFV). This study used immunoinformatics for the rapid and inexpensive designing of a safe and effective multi-epitope subunit vaccine for ASFV. A total of 18,858 proteins from 100 well-annotated ASFV proteomes were screened using various computational tools to identify potential epitopes, or peptides capable of triggering an immune response in swin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 129 publications
0
4
0
Order By: Relevance
“…The final construct was docked using the ClusPro server. The TLR4- fMEVc complex had the highest binding affinity at a ΔG of −18.6 kcal/mol compared to the controls, TLR4- Brucella lumzaine synthase, and TLR4- M. tuberculosis RpfE and TLR4- S. pneumoniae DnaJ, with a binding energy of −9.9 kcal/mol, −9.7 kcal/mol, and −13.1 kcal/mol, respectively ( Simbulan et al ., 2024 ). Ligplot and PDBsum predicted 24 hydrogen bonds between the vaccine construct and TLR4 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The final construct was docked using the ClusPro server. The TLR4- fMEVc complex had the highest binding affinity at a ΔG of −18.6 kcal/mol compared to the controls, TLR4- Brucella lumzaine synthase, and TLR4- M. tuberculosis RpfE and TLR4- S. pneumoniae DnaJ, with a binding energy of −9.9 kcal/mol, −9.7 kcal/mol, and −13.1 kcal/mol, respectively ( Simbulan et al ., 2024 ). Ligplot and PDBsum predicted 24 hydrogen bonds between the vaccine construct and TLR4 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The primary benefit of this technology is its ability to detect many candidate vaccinations without spreading bacterial illnesses across a wet laboratory [ 22 ]. Several instances of how vaccinosis has been used to construct a multi-epitope-based vaccination method include Acinetobacter baumannii [ 16 ], MERS-CoV, HIV, and SARS-CoV-2 [ 22 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown the beneficial use of RV, highlighting the need for vaccination as a preventive and cost-effective strategy against this virus. Researchers used reverse vaccinology and subtractive proteomics techniques in this study to ascertain prospective therapeutic interventions for A. baumannii [ 11 , 16 , 43 ]. The recombinant chimeric peptide vaccine demonstrated a 50% efficacy in hamsters against the pathogen during recent in vitro testing [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Due to its high morbidity and mortality rates, the disease has resulted in substantial economic losses and presents an ongoing threat to food security, particularly in developing countries. 8,9 There is neither a cure nor vaccine commercially available for ASF, 2,10 and its control relies solely on biosecurity protocols, such as animal quarantine and culling of infected swine. 2,11 However, these methods entail negative economic implications.…”
Section: Introductionmentioning
confidence: 99%